The Urgency of Legal Regulation on the Use of Artificial Intelligence in Digital Marketing Practices in Indonesia - Datu, Moh. Azwar Andi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The purpose of this study is to analyze the legal status of Artificial Intelligence (AI) in digital marketing practices in Indonesia and assess the urgency of establishing specific legal regulations governing its fair and accountable use. As digital technology advances, AI is increasingly being used by businesses to automate promotional processes, personalize advertising, and analyze consumer behavior through large-scale data processing (big data analytics). However, the use of AI in this context raises complex legal issues, particularly regarding personal data protection, legal liability, and algorithmic transparency. This study uses a normative juridical approach by analyzing various relevant laws and regulations, including Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law), Law Number 8 of 1999 concerning Consumer Protection, and Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). The results of the study indicate that in Indonesia's positive legal system, AI is still viewed as a legal object (instrumental entity) that does not have independent responsibility. Therefore, all legal consequences of its use remain the responsibility of businesses, developers, or electronic system organizers. Based on this, this study confirms that a specific legal framework regarding AI is needed that emphasizes the principles of transparency, accountability, fairness, and protection of digital privacy rights, so that the use of AI in digital marketing can take place ethically, responsibly, and in accordance with the principles of national legal certainty.